Situation of Public Health Management in Area of Tambon Administration Organization (TAO) of Chonburi Province - Tanvatanakul, Vasuton; Saowakontha, Sastri; Amado, Joao (Journal of Health Science of Thailand, 2019)
Research objectives were to study phenomenon and movement of health activities, and relationship to situation of public health management during March - September 2003. The data was collected from 422 respondents, selected by multistage sampling from various groups of community members of 5 different tambon administration organizations level 1-5 and different districts of Chonburi province. The results showed the phenomenon of health activity that had impact on health policy, quality of life, health development experience, mass communication were mostly high (48.6, 50.2, 50.5 and 89.8% respectively); trend of problem change, alternative health, social movement health resource, were mostly in moderate condition (49.8, 50.7, 58.5 and 73.3% respectively). The movement of health activities in terms of health development spiritual and health perception, were mostly high (48.6% and 77.0% respectively) Whereas, Health knowledge, health development willingness, health interest, health development idea, were mostly at moderate condition (55.9, 60.0, 67.3 and 79.2% respectively). In addition, high level of public health management (49.3%) was reported. The analysis of correlation between each subvariable of phenomenon, movement of health activities and situation of public health management showed significant association (p <0.001) in every subvariable. Based on the results, sub-district administration organizations should be encouraged to accommodate more phenomenon and movement of health activities while strengthening their development potential and ability in carrying out health activities and community development.